Enhanced electricity generation and tetracycline removal of bioelectro-Fenton with electroactive biofilm induced by multi external resistance. (February 2022) - Song, Xiangru; Jo, ChungHyok; Zhou, Minghua
Abstract: A simple multi electric resistance mode is used to regulate electroactive anode film, which improves the electricity generation, H2 O2 production and pollutants removal. This external electron transport path (double cathode with different resistance) exhibits higher H2 O2 production (571.9 ± 0.1 mg m −2 h −1 ), tetracycline removal (71.4 ± 0.4% to 50 mg L −1 ), and power (615.3 ± 9.9 mW m −2 plus 680.6 ± 10.3 mW m −2 ), which is 75.4%, 23.1% and 1.25 times higher than that of single cathode mode. The double cathode improves the relative abundance of Geobacter (exoelectrogens), which is 9.45 times higher than that of single cathode mode. The anodic capacitance of double cathode mode is more than 10 times higher than that of single cathode mode. Electrons (generate by exoelectrogens) participate in two- (cathodic chamber) and four- (anodic chamber) electron reaction at cathode surface, and facilitates electricity generation of bioelectro-Fenton. The removal rate of double cathode mode is 342.7 mg L −1 d −1 (50 mg L −1 tetracycline) and 170.1 mg L −1 d −1 (20 mg L −1 tetracycline), which is much higher than that of reported. These results indicate that external electron transport path enhances the electrochemical activity of anode film and performance of bioelectro-Fenton. This paper provides a new power supply method for the future practical application and field experiment of bioelectrio-Fenton. Graphical abstract: Image 1 Highlights: External electron transport pathway promoted performance of BEF. H2 O2 production and tetracycline removal was improved by double cathode. Relative abundance of Geobacter was increased after using double cathode. Removal rate of DBEF was 342.7 mg L −1 d −1 to 50 mg L −1 TC.